2022
DOI: 10.1155/2022/6723326
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomic Risk Factors for Osteochondral Fracture of Acute First-Time Patellar Dislocation in Adolescents: A Retrospective Magnetic Resonance Imaging Study

Abstract: Objective. To analyze the risk factors for osteochondral fracture (OCF) of first-time acute patellar dislocation (APD) through measurements of patellofemoral anatomy in adolescents. Methods. In this prospective study, all patients were divided into two groups according to whether OCF was detected on magnetic resonance imaging (MRI): Group A (associated with OCF) and Group B (without OCF). Patellofemoral anatomy was evaluated with four aspects including trochlear/patellar dysplasia, patella location, patellofem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 38 publications
0
9
3
Order By: Relevance
“…Although the mechanism of injury was not found to be an independent risk factor in the logistic regression analysis, this finding demonstrated that the risk of developing OCF in APD is multifactorial, and the mechanism of injury is one of these factors. Li et al 16 found no relationship between the risk of OCF and the mechanism of injury. Although the mechanism of injury has not been evaluated in other studies, it has been reported that highenergy dislocations in the patellofemoral joint may cause OCF due to the greater force exerted on the cartilage surface.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although the mechanism of injury was not found to be an independent risk factor in the logistic regression analysis, this finding demonstrated that the risk of developing OCF in APD is multifactorial, and the mechanism of injury is one of these factors. Li et al 16 found no relationship between the risk of OCF and the mechanism of injury. Although the mechanism of injury has not been evaluated in other studies, it has been reported that highenergy dislocations in the patellofemoral joint may cause OCF due to the greater force exerted on the cartilage surface.…”
Section: Discussionmentioning
confidence: 97%
“…None of the previous studies investigating the causes of OCF in APD have evaluated the presence of joint hypermobility. [14][15][16][17] Joint hypermobility is seen in patients with hyperlaxity due to ligament and connective tissue laxity. Therefore, joint subluxations and dislocations may occur even in minor traumas in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations